COMMODITIES SPACE FOR SOCIAL INTERACTION IN THE KAMPUNG AROUND CAMPUSES AT JAKARTA - Ramos P Pasaribu; Uras Siahaan; Rumiati Rosaline Tobing (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2017)
An interesting phenomenon in Indonesia today is that